PERISTIWA CAMPUR KODE DALAM PEMBELAJARAN BAHASA INDONESIA SISWA KELAS X SMK N 1 KASIHAN BANTUL TAHUN AJARAN 2014-2015 - Desy Rufaidah (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2016)
This study aimed to describe and explain the forms and factors that cause code-mixing case on Indonesian speaking skills class X SMK N 1 Kasihan Bantul. The data of study is orally data. The data is sourced from the spoken language student class X SMK N 1 Kasihan Bantul contained code-mixing in learning Indonesian. The data obtained by free scrutinize of statement involvement technique, and interviews. The data validation using key informants review technique and data base composition. The data analysis technique using analysis Â interactive model, the data is analyzed using replacement techniques. The results showed that the form of code-mixing in Indonesian speaking skills class X SMK N 1 Kasihan Bantul is words, phrase, word repetition, and baster. The factors that causing the code-mixing is the identification of the role, and the identification of varieties.Keywords: code-mixing case, class X SMK N 1 Kasihan Bantul